Implementasi Pendidikan Iman dan Adab di Kelompok Bermain untuk Stimulasi Perkembangan Nilai Agama dan Moral Anak - Nia Kurniasari; Armanila Armanila (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
Faith and etiquette education in early childhood is important to provide because children's religious and moral character is in the imitative stage, and thus, it needs to be directed towards good habits. The aim of this research is to describe the implementation of faith and etiquette education in a Playgroup setting to stimulate the development of religious and moral values in children. The research method used is qualitative descriptive with a field research approach. The research subjects are 15 children aged 3-5 years in the Halimah As-Sa'diyah Banguntapan Playgroup. The research participants include the foundation chairman, school principal, class teachers, and representative parents. Data collection is done through interviews, observations, and documentation. The results of this research show that the implementation of faith and etiquette education can stimulate the development of religious and moral values in children through habituation methods, storytelling methods, performance methods, field trip methods, role-playing methods, and exemplary methods. The achievement of children's development in religious and moral values shows that 33% (5 children) have shown progress, and 67% (10 children) have developed as expected.